Treating performance of a commercial-scale constructed wetland system for aquaculture effluents from intensive inland Micropterus salmoides farm - Li, Bing; Jia, Rui; Hou, Yiran; Zhu, Jian (Frontiers in Marine Science, 2022)
In intensive inland fish farming, discharge of untreated effluents adversely affects adjacent water bodies and causes water pollution. Thus, it is highly necessary to treat the effluents from inland fish farm. In this study, we built a commercial-scale integrated constructed wetland (CW) system with vertical subsurface flow, and monitored the purifying effect. During fish farming and discharge of effluents periods, the water samples were collected to detected the total nitrogen (TN), total phosphorus (TP), ammonia nitrogen (NH4+-N), nitrate nitrogen (NO3–N), nitrite nitrogen (NO2–N) and chemical oxygen demand (CODMn). Results showed that the system was stable and significantly improved water quality from fish pond. During the fish farming period, the removal efficiency for TN, TP, NH4+-N, NO3–N, NO2–N, and COD was 24.93–43.72%, 61.92–72.18%, 56.29–68.63%, 56.66–64.81%, 56.42–64.19% and 28.37–42.79%, respectively. Similarly, these parameters were also markedly decreased by the integrated CW system during sewage discharge period, and the average total removal rate for TN, TP, NH4+-N, NO3–N, NO2–N, and COD was 50.24 %, 64.48%, 61.36%, 62.65%, 56.16% and 37.32%, respectively. It was worth noting that three key parameters for effluents detection TN, TP and COD values were below the threshold values of water quality of Class Ⅱ in freshwater sewage discharge standard of China (SCT9101-2017). In conclusion, this study evidently demonstrated that application of CW system was an environmental sustainable sewage treatment strategy in intensive inland fish farming.